Rapid changes of dust geochemistry in the Saharan Air Layer linked to sources and meteorology. (15th February 2020) - Rodríguez, Sergio; Calzolai, Giulia; Chiari, Massimo; Nava, Silvia; García, M. Isabel; López-Solano, Javier; Marrero, Carlos; López-Darias, Jessica; Cuevas, Emilio; Alonso-Pérez, Silvia; Prats, Natalia; Amato, Fulvio; et al.
Abstract: Based at Izaña Observatory ( 2400 m a.s.l. in Tenerife), we performed 1-h resolution measurements of elemental composition of dust in the Saharan Air Layer (SAL) and studied the variability of the ratios of these elements to aluminium (elemental ratios). In a period ( 1 week) of continuous dust presence (50–200 μg/m 3 ), we observed rapid variations of dust composition; some elemental ratios changed by a factor 2 in a few (5–8) hours. The lowest variability (Normalized Variability Range, %) was found for Si/Al (9%) and Fe/Al (9%), followed by the ratios of K, Ti, Mg, Mn, Ca and Sr to Al (20–80%), and the highest for S/Al, Na/Al and Cl/Al (110–160%) and a number of trace metals (Cr, Cu, Ni, Zn, Zr) and Br (>200%). This variability was induced by the alternating impacts of three of the large North African dust sources: NE Algeria (rich in evaporite minerals bearing Ca, S, Sr, K and Mg and in illite mineral), Western Sahara to Bechar region (containing Na, S and Cl rich Yermosol soils) and SW Sahara – Western Sahel (rich in illite and hematite). We traced the variability in large-scale meteorology using the so-called North African Dipole Intensity (NAFDI: strength of the subtropical Saharan high -Morocco-to the monsoon tropical low -Nigeria-). The mobilization of dust from the different sources was associated with westward propagating Harmattan pulses linked to the change of phase of NAFDI (- to +), the associated westward shifts of the Saharan Heat Low and convective monsoon inflow. We found a correlation between dust composition in the SAL and NAFDI: moderate NAFDI values (0 to +2.5) were associated with Ca, K, Na, Mg and S rich dust linked to dust sources in NE Algeria, whereas higher NAFDI values (+2.5 to +4) were linked to Fe rich dust (Ca, Na and S depleted) linked to dust sources in SW Sahara – Western Sahel. The results of this study also show that some trace elements (Br, Cr, Ni, Zn and Zr) are influenced by industrial emissions into North Africa. Graphical abstract: Image 1 Highlights: Dust composition changes rapidly, 5–8 h, in the Saharan Air Layer. North African Dipole Intensity NAFDI traces the variability of summer meteorology. Positive phase of NAFDI enhances dust export to the North Atlantic. Negative phase of NAFDI enhances dust export to the Western Mediterranean. NAFDI connects meteorology, sources and dust composition in the Saharan Air Layer.